The establishment of solid mutant line from somaclonal variation generated through mature petal cultures of chrysanthemum - Kaewkam, A.; Limsanguan, P.; Chansuthep, S.; Chanprame, So.; Chanprame, Se. (International Journal of Agricultural Technology, 2022)
The mature petals from ray florets of ‘Polaris Pink’ chrysanthemum were cultured in vitro on Murashige and Skoog (MS) medium containing various combinations and concentrations of BA and 2,4-D. The MS medium supplemented with 1 mg/L BA and 1 mg/L 2,4-D yielded the highest efficiency of callus formation after 2 months of culture. The calli were then subjected to shoot regeneration on MS solid medium containing various concentrations of kinetin for shoot induction. The highest number of regenerated shoots was obtained on MS medium supplemented with 2 mg/L kinetin. Using MS medium supplemented with 2 mg/LBA and 0.5 mg/L 2,4-D resulted in somaclonal variation induction. The flower color of the variant line changed from light pink to light purple and the tip of petal was rounder than that of control. The solid variant lines were obtained through several generations of in vitro single node cutting. The SRAP showed that the primer pair Me1/Em10 exhibited the polymorphic band between the mother plant and variant plant.